If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 11 = 15 + -6b Reorder the terms: 11 + 2b = 15 + -6b Solving 11 + 2b = 15 + -6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '6b' to each side of the equation. 11 + 2b + 6b = 15 + -6b + 6b Combine like terms: 2b + 6b = 8b 11 + 8b = 15 + -6b + 6b Combine like terms: -6b + 6b = 0 11 + 8b = 15 + 0 11 + 8b = 15 Add '-11' to each side of the equation. 11 + -11 + 8b = 15 + -11 Combine like terms: 11 + -11 = 0 0 + 8b = 15 + -11 8b = 15 + -11 Combine like terms: 15 + -11 = 4 8b = 4 Divide each side by '8'. b = 0.5 Simplifying b = 0.5
| 3x+13=-74 | | 8x-5=-5x+5 | | 2x=(3x-2)(m+4) | | 2w+(2w+13)=54 | | 8x-(3x-5)=433 | | 9x^2+4x=12x | | 7+4(t-9)=2(t+6)+5 | | 12s^2+s-35= | | 9=5x+6 | | 4944=48(-32+x) | | x(x-9)+20=0 | | 980=-98p | | p(t)=-3t^2-7t-8 | | x+(x+13)=54 | | x=0.8x+2.8 | | 4a^2-144=0 | | 6p=228 | | 5-x-2=3 | | x=6x+3x | | 10x+6=2x+44 | | 6+4(1+3x)=7(x-5) | | 55=-7x+6 | | -1.4(-4p-1)+4.4p= | | 9y-3=7y+1 | | 4x+7=7(x+1)-3x | | 26-(3x-10)=6 | | 4-36= | | -4+-61= | | -1.4(-4p-1)+4.4= | | d+9-90=-5 | | -2(4-3z)-7=6(z+1) | | 2x-(24-x)=-6 |